2021
DOI: 10.1055/s-0041-1734570
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Surgical Splints in Orthognathic Surgery: A Bibliometric Study

Abstract: Introduction Orthognathic surgeries require the use of surgical splints (SS) to stabilize the occlusion and the segments fixed with plates and screws. Technological advances in the field of computing and the possibility of generating three-dimensional (3D) images have brought different possibilities for making SS, which has generated greater predictability and customization of surgical plans. The bibliometric study can have a qualitative character through the scope of articles in a certain area of knowledge. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…Recent bibliometric analysis revealed that contemporary studies related with orthognathic surgery topics are mostly concentrated around usage of computer-aided technologies during complex treatment, virtual planning and modifications of surgical splints with the aim to personalize treatment sequence [1,2]. Even though virtual treatment planning and use of 3D printing technology have not became obligatory within orthognathic surgery, but it is already established that such approaches largely increase level of treatment individualization and help to achieve better patientoriented outcomes [3].…”
mentioning
confidence: 99%
“…Recent bibliometric analysis revealed that contemporary studies related with orthognathic surgery topics are mostly concentrated around usage of computer-aided technologies during complex treatment, virtual planning and modifications of surgical splints with the aim to personalize treatment sequence [1,2]. Even though virtual treatment planning and use of 3D printing technology have not became obligatory within orthognathic surgery, but it is already established that such approaches largely increase level of treatment individualization and help to achieve better patientoriented outcomes [3].…”
mentioning
confidence: 99%